The Influence Of Mediation Factors Between Entrepreneurship Education And Entrepreneurial Intentions: A Systematic Literature Review - Rauf, Rusdiaman; Jones, Eric Alan (Journal of Economic Education, 2025)
Entrepreneurship education is designed to improve knowledge, skills, and an entrepreneurial mindset. However, the impact on entrepreneurial interest is not always direct, but is influenced by factors that mediate the relationship between entrepreneurial education and entrepreneurial intention. This study aims to provide a comprehensive overview of the factors that mediate the relationship between entrepreneurship education and entrepreneurial intentions. This study using Systematic Literature Review as the method. The findings: (i) Entrepreneurship education has the potential to be a powerful tool to foster entrepreneurial  intentions and encourage economic growth and innovation, (ii) Entrepreneurship education influences individual attitudes and behaviors in creating new entrepreneurs, (iii) Effective entrepreneurship education can motivate entrepreneurial intentions through the role of contextual factors such as culture, gender, socioeconomic background, and environment (iv) A pedagogical approach is needed in designing curriculum, and learning outcomes related to entrepreneurship education initiative. Entrepreneurship education has an effect on entrepreneurial intention if it is supported by an effective pedagogical approach.